A Taste of England - David, Elizabeth (Petits Propos Culinaires, 2025)
This text was purchased at the sale in November 2000 of selected manuscripts, typescripts, books and memorabilia belonging to, written by or relating to Elizabeth David. The catalogue, and Elizabeth David’s literary executor; Jill Norman, state that it has not been published elsewhere, though attentive readers may find echoes of its message in other writings. The typescript is a top copy with occasional MS amendments by the author. It bears the stamp of David Higham Associates Ltd., her literary agents. It is double-spaced, single-sided, occupying seventeen quarto folios. The piece was evidently planned as three successive articles, and Elizabeth David had made provision for the insertion of sub-headings. I have printed it as found (with a few tiny adjustments which I hope the author would not have railed against), incorporating the author’s original corrections but omitting the various notes regarding sub-headings or sub-division. There is no indication of the date of its composition but I posit that it was around 1964. Copyright remains with the Estate of Elizabeth David.